Gingival Thickness Assessment: Visual versus Direct Measurement - Roya Shariatmadar Ahmadi; Rastin Tavassoli; Ferena Sayar; Katayoun Ghaffari; Fatemeh Sarlati (Islamic Dental Association of Iran, 2016)
Background and Aim: Several methods have been suggested to measure gingival thick-ness. This study aimed to assess the reliability of visual assessment of facial gingival biotype of maxillary and mandibular teeth with or without using a periodontal probe in comparison with direct measurement. Materials and Methods: Sixty-seven healthy patients (25 women and 42 men) with a total of 100 hopeless teeth were selected for this study. Three methods were used to evaluate gingival thickness namely visual assessment, visual assessment with the use of periodontal probe and direct measurement using a caliper after extracting the hopeless tooth. One trained examiner performed all examinations. Patient demographics, tooth position, and the results of three assessments were recorded. The mean and standard deviation of gingival thickness were calculated. The three methods were compared using the chi-square test. Results: The accuracy of visual assessment method for the "thin biotype" was 96.7% [positive predictive value (PPV)=96.7%], while it was 10.3% for "thick biotype" [negative predictive value (NPV)=10.3%]. The accuracy of visual assessment with the use of periodontal probe for the thin biotype was 100% (PPV=100%), while it was 17.1% for the thick biotype (NPV=17.1%). The results of visual assessment method alone and with the use of periodontal probe were incorrect in 37% and 29% of the cases, respec-tively and this difference was significant (P<0.01). Conclusion: Gingival biotype identification by assessment with the use of periodontal probe is an adequately reliable method while visual assessment of gingival biotype by itself is not sufficient for proper diagnosis. Key Words: Gingiva, Periodontium, Mouth Mucosa